2011
DOI: 10.1212/wnl.0b013e31823152c3
|View full text |Cite
|
Sign up to set email alerts
|

Congruence and discrepancy of interictal and ictal EEG with MRI lesions in focal epilepsies

Abstract: The occurrence and localization of interictal and ictal EEG findings differs vastly for lesions in different brain regions. These findings should be used to carefully weigh the results from EEG studies particularly in patients with extratemporal epilepsies considered for epilepsy surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 31 publications
7
36
0
6
Order By: Relevance
“…verschiedene Aktivierungsmethoden führen zu einer höheren Wahrscheinlichkeit für das Auftreten von ETPs [24]. Bei wenigen M a n u s c r i p t Oberflächen-EEG typischerweise keine ETP aufgezeichnet [26].…”
Section: Nachweis Von Etp Im Interiktalen Eegunclassified
“…verschiedene Aktivierungsmethoden führen zu einer höheren Wahrscheinlichkeit für das Auftreten von ETPs [24]. Bei wenigen M a n u s c r i p t Oberflächen-EEG typischerweise keine ETP aufgezeichnet [26].…”
Section: Nachweis Von Etp Im Interiktalen Eegunclassified
“…These are EEG seizure patterns that have typical rhythmic theta in the temporal regions as in MTLE, but actually represent spread from a distant epileptogenic site that may not be well localized on EEG. One study reported that 11% of patients with an extratemporal MRI lesion had ictal temporal seizure patterns (Remi et al 2011). Pseudotemporal ictal patterns have been reported for nearly all anatomic localizations (i.e., orbitofrontallobe, parietal lobe, occipital lobe, etc.).…”
Section: Pseudotemporal Patterns and Benign Variantsmentioning
confidence: 99%
“…Kontinuierliches Video-EEG-Monitoring kann die diagnostische Ausbeute deutlich erhö-hen [26]. [11,21] und dem Aurastatus. Hier zeigt das Oberflächen-EEG nur in ca.…”
Section: Status Epilepticusunclassified